Changes in Selected Immunological Parameters and Oxidative Stress Responses in Different Organs of Oncorhynchus mykiss Exposed to Ivermectin - Sakin, Fatih; Yonar, Serpil Mise; Yonar, M. Enis; Saglam, Naim (Revista Chimie Srl, 2012)
In this study, effects of ivermectin on selected immunological parameters, oxidative stress, and antioxidant status in the blood, liver, kidney, heart, and spleen of the rainbow trout (Oncorhynchus mykiss) were examined. Ivermectin was administered intraperitoneally at single doses of 0.01 and 0.02 mg ivermectin kg(-1) fish. Blood and tissue samples (liver, kidney, heart, and spleen) were then removed on days 3, 7, 10, and 14 for immunological and biochemical analyses. The immunological parameters measured were numbers of leucocytes (WBC), nitroblue tetrazolium activity (NBT), total plasma protein (TP), and total immunoglobulin (TI). Malondialdehyde (MDA) values were measured in the liver, kidney, heart, and spleen tissues as indexes of oxidation, and the activities of catalase (CAT), reduced glutathione (GSH), glutathione peroxidase (GSH-Px), and superoxide dismutase (SOD) were measured as indexes of antioxidant status. The results showed a decrease in the WBC value, NBT activity, and TP and TI levels after the injection of 0.01 and 0.02 mg ivermectin kg(-1) fish (p <0.05, 0.01, 0.001). Our results suggest that ivermectin at these doses causes oxidation in fish liver, kidney, heart, and spleen tissues due to impairment of the antioxidant system.
Keywords: Rainbow trout; ivermectin; immunological parameter; antioxidant status; oxidative stress; pesticide; antiparasitic drug